Theoretical study of the structural stability, electronic and magnetic properties of XVSb (X = Fe, Ni, and Co) half-Heusler compounds - M. Mokhtari; F. Dahmane; G. Benabdellah; L. Zekri; S. Benalia; N. Zekri (Condensed Matter Physics, 2018)
The structural, electronic and magnetic properties of half-Heusler compounds XVSb (X = Fe, Co and Ni) are investigated by using the density functional theory with generalized gradient approximation (GGA), and Tran-Blaha modified Becke-Johnson (TB-mBJ) exchange potential approximation. It is found that the half-metallic gaps are generally reasonably widened by mBJ as compared to the GGA approximation. The magnetic proprieties of XVSb (X = Fe, Co and Ni) are well defined within mBJ with an exact integer value of magnetic moment. The band gaps given by TB-mBJ are in good agreement with the available theoretical data. The FeVSb exhibits a semiconductor nature. The CoVSb and NiVSb present half-metallic behaviour with total magnetic moment of 1μ_B and 2μ_B in good agreement with Slater-Pauling rule. These alloys seem to be a potential candidate of spintronic devices.